2003
DOI: 10.1016/s0169-2607(01)00199-7
|View full text |Cite
|
Sign up to set email alerts
|

The computer simulation of wear behavior appearing in total hip prosthesis

Abstract: Computer algorithms are proposed for the estimation of wear appearing in artificial hip joints using finite element analysis based on the modified Archard's wear law, contact features and an analogue wear process. A pin-on-disk plate experiment is reconstructed to assess the efficiency and validity of the algorithms proposed here. Through the successful verification of wear depth and volume loss of the pin-on-disk plate as well as the artificial hip joint, the current algorithms provide significant agreement w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 28 publications
5
67
0
Order By: Relevance
“…Recent data from the National Joint Registry (NJR) indicates that around 89,000 hip operations were performed in the UK using arthroplasty in 2013 (11 th Annual Report 2014, NJR for England, Wales and Northern Ireland, 2014). The American Academy of Orthopaedic Surgeons (AAOS) has indicated that more than 285,000 THRs are performed each year in the United States (National Hospital Discharge Survey, USA, 2010).…”
Section: Fig 1 Schematic Of Total Hip Replacement In Situmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from the National Joint Registry (NJR) indicates that around 89,000 hip operations were performed in the UK using arthroplasty in 2013 (11 th Annual Report 2014, NJR for England, Wales and Northern Ireland, 2014). The American Academy of Orthopaedic Surgeons (AAOS) has indicated that more than 285,000 THRs are performed each year in the United States (National Hospital Discharge Survey, USA, 2010).…”
Section: Fig 1 Schematic Of Total Hip Replacement In Situmentioning
confidence: 99%
“…Many studies have been published on determining wear in prosthetic devices which have mainly focused on the articulating surfaces between the head and acetabular (plastic) cup [4][5][6][7][8][9][10][11]. Modern large diameter Metal-on-Metal (MoM) THRs were introduced around 1997 [12] as an option for young active patients to provide a device with reduced wear debris and risk of dislocation, greater strength and longer life than Metal-on-Plastic (MoP) types.…”
Section: Fig 1 Schematic Of Total Hip Replacement In Situmentioning
confidence: 99%
“…A computational algorithm developed in our pre vious studies [28] is followed to evaluate the wear rate of the acetabular cup. This algorithm includes three major parts, namely, determination of contact stress at the articulating surface, estimation of local wear depth, and updating the contact geometry.…”
Section: Computational Processmentioning
confidence: 99%
“…In particular, for the THR with a UHMWPE polymeric component the wear simulation is based on the classical Archard equation together with all other studies reported in literature referred to, for example, in [6,7,8], where the wear factor is taken as a constant value. In [5], the polymer wear in terms of cumulative linear and volume wear when the wear factor is chosen to be a function of contact pressure was first evaluated.…”
Section: Introductionmentioning
confidence: 99%